Psychosocial effects of participation in rituals of transitional justice - Beristaín, Carlos Martín (2010)
This article examines the effects of participation in transitional justice rituals. Truth Commissions and trials have instrumental goals of distributive justice, and serve as rituals given their marked symbolic character, helping to achieve reconciliation and the reconstruction of social norms. Evidence suggests that participation in trials increases negative emotion and negative emotional climate. However participants in such rituals have evidenced increased empowerment, despite conditions of limited justice and reparation. Moreover, participation in Gacaca or popular trials in Rwanda, decreases shame in victims, and decreases negative stereotypes and increases individualization of out-groups. Finally, a collective analysis of 16 Latin America nations found that trials and a successful Truth Commission reinforces respect for human rights.